Relationship lending: That ship has not sailed for community banks - Dmytro Holod; Joe Peek; Gökhan Torna (Federal Reserve Bank of Boston, 2024)
This study provides direct evidence of the value to banks arising from relationship lending by estimating the market premium placed on banking organizations' small business loan portfolios. Using data from the small business loan survey contained in the June bank Call Reports, we find that small commercial and industrial (C&I) loans add value to community banks both in absolute terms and relative to the value contributed by larger C&I loans. The value-enhancing effect of small business loans is observed primarily at small community banks, and it was present during the Great Recession as well as during periods of more normal economic conditions. Furthermore, the value creation emanates primarily from the smallest relationship-based C&I loans, those with original values of 100,000 or less, and at the smallest community banks. By contrast, small commercial real estate (CRE) loans, being relatively more transactional than C&I loans, do not contribute additional value to community banking organizations. The evidence is consistent with a positive role played by small banks making relationship-based loans to small firms.
Keywords: G21; G28; G31; 330; Small business lending; relationship lending; bank value; community banks; commercial and industrial (C&I) loans; commercial real estate (CRE) loans